Struktur Komunitas Bentik di Area Terumbu Karang Buatan Pulau Karya, Kepulauan Seribu - An Nisa Nurul Suci; Ahmad Taufik Ghozali; Firdha Iresta Wardani; Ana Ariasari; Nella Tri Agustini; Nur Lina Maratana Nabiu; Akbar Abdurrahman Mahfudz; Muamar Mujab; Akhmad Adib; Neni Meirawati; Maretha Dwi Villany (Cenderawasih University, 2023)
Coral reef conservation can be conducted by creating artificial coral reefs as was done on Karya Island. Monitoring and evaluation afterwards is needed. This study aims to determine the benthic community structure in the concrete module area, Karya Island artificial reef after 15 years of coral transplantation. Data collection was carried out using the photo transect method on line transects (50 m) in 3 stations. The transect images taken were then processed using CPCe. The condition of the coral reefs at the study site was in the bad category with a percentage of live hard coral cover of 13.39 ± 4.62%. The highest to lowest percent cover respectively were DCA (51.67 ± 6.60%), SP (15.50 ± 7.93%), FS (14.72 ± 5.98%), HC ( 13.39 ± 4.62%), SC (4.05 ± 2.76%), and OT (0.67 ± 0.35%). Benthic community diversity in St. 1 (H'=1.59) and St. 3 (H'=1.52) is moderate, while St.2 has low diversity (H'=0.84). The benthic community at St.1 and St.3 is classified as stable with a uniformity value of 0.72 and 0.78 respectively. However, St.2 has an unstable community (E=0.40). Dominance appears in St. 2 (C=0.66) due to high abundance of Padina sp. is much higher than other species.